2019
DOI: 10.30874/comdev.2018.88
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Celebrity Endorser on Purchasing Intention of Halal Cosmetic [Peran Celebrity Endorser Terhadap Minat Beli Kosmetik Berlabel Halal]

Abstract: Purpose of this study is to analyze the influence of attractiveness, credibility, and expertise on buying an interest in buying halal labeled cosmetics. This study used a quantitative approach. The population of this research is consumers who purchase Wardah halal label cosmetics in Semarang City which has been an unknown number then the number of samples is searched by the Isac Michel formula and samples taken 100 respondents. The type of data used is the primary data which sourced from questionnaires that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results of this study are in line with previous research conducted by Rachbini (2018) which found that in the Chinese-made smartphone industry in Indonesia, celebrity endorsers can positively influence people's intentions both now and in the future. The results of this study are also in line with the statement of Adinugraha et al, (2018) found that halal cosmetic products in Indonesia also found that celebrity endorsers positively influence a person's purchase intention of a brand.…”
Section: The Effect Of Celebrity Endorser To Investment Intentionsupporting
confidence: 90%
“…The results of this study are in line with previous research conducted by Rachbini (2018) which found that in the Chinese-made smartphone industry in Indonesia, celebrity endorsers can positively influence people's intentions both now and in the future. The results of this study are also in line with the statement of Adinugraha et al, (2018) found that halal cosmetic products in Indonesia also found that celebrity endorsers positively influence a person's purchase intention of a brand.…”
Section: The Effect Of Celebrity Endorser To Investment Intentionsupporting
confidence: 90%
“…Endorsers are ad supporters or known as ad stars to support a product to be. The endorsement is where celebrities act as spokespersons and support the brand with all attributes of popularity, personality, and social status of the celebrity [14]. So this endorsement has an impact on the brand of the product and influences the community.…”
Section: Celebrity Endorsementmentioning
confidence: 99%
“…Endorsement itself has a meaning, namely communication activities or introducing a product brand, where the celebrity acts as a spokesperson and supports the brand with all the attributes of popularity, personality, and social status of the celebrity. Endorsers or celebrity endorsers are people who value a product or convey a message in an advertisement with the aim of attracting consumer interest (Adinugraha et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%